PREVALENCE OF METHICILLIN RESISTANT STAPHYLOCOCCUS AUREUS IN WESTERN TAMILNADU: Life Sciences-Microbiology - GANDHIRAJ .D; WESELY E .G; PALANISAMY.A; SAHANAPRIYA .S (International Journal of Life Science and Pharma Research, 2022)
Humans are natural reservoir for Staphylococcus aureus, and asymptomatic colonization is far more common than infection. Colonization byStaph.aureusmay be persistent and can last for years. Recent reports of strains of Methicillin Resistant Staphylococcus aureus (MRSA) isolated from community have led speculation that the epidemiology of S. aureus is changing .Usually, MRSA infections havebeen a concern among hospitals for decades now and the reports revealthat the community acquired MRSA is increasing . The community acquired strains could possibly have arisen as a consequence of resistance gene transfer from a hospital acquired (nosocomial) donor into a susceptible recipient. With appropriate analysis of donor andrecipient chromosomes, it could be possible to determine whether these newly identified communityacquired strains are wild or self-supporting.The present study was conducted with a total sample of 1296 wound and other skin infection samples that were collected from different hospitals in western Tamilnadu. The specimens were inoculated in blood agar for isolation and identified as S.aureus by using standard method based on colony morphology, Gram’s stain, catalase and coagulase test. A total 258 isolates were confirmed as S.aureus. These strains were processed by the following three techniques,(i) oxacillin, Methicillin and cefoxition disk diffusion method, (ii) cultured in MeRSA plate, (iii) Vitek 2 fully automated ID and AST system for detection mecA gene producer. 34 MRSA strains were identified out of 258 strains.